Determinan Minat Mahasiswa Akuntansi Memilih Karir Entrepreneur dengan Pendidikan Kewirausahaan Sebagai Variabel Intervening (Studi Empiris Pada Mahasiswa STIE Surakarta) - Octavia, Dewi Ika; Susanti, Ari; Saputra, Era Trianita (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
This study aims to determine the effect of family environment, business capital and entrepreneurial motivation on interest in entrepreneurship with entrepreneurship education as the intervening variable among students of STIE Surakarta. This research is a quantitative research using research objects of accounting students at STIE Surakarta by distributing questionnaires to respondents who were randomly selected. The population of this study was 559 respondents with random sampling by determining the number of samples in this study using Slovin's formula. The SEM-PLS (Structural Equation Modeling - Partial Least Squares) data analysis method uses the SmartPLS 6.0 program. The results of this study indicate that family environment, business capital, entrepreneurial motivation have a positive effect on entrepreneurship education. Entrepreneurial motivation has a positive effect on students' interest in entrepreneurship. Home environment has a positive effect on student interest in accounting Entrepreneurship education fails to mitigate the influence of home environment and business capital on student interest in accounting for entrepreneurship, but it can dampen the influence of entrepreneurial motivation on entrepreneurship. interest of accounting students in entrepreneurship at STIE Surakarta.